Gender integration and intersectionality in food systems research for development: A guidance note - McDougall, Cynthia; Newton, Julie; Kruijssen, Froukje; Reggers, Amy (WorldFish, 2022)
This Guidance Note highlights key points for gender integration in the research for development (R4D) project cycle. It uses an intersectional lens to recognize how aspects of social identity such as age or life stage, class, caste, ethnicity, ability, sexual orientation and so forth crosscut and shape gender and power. It provides an overall introduction, guide and set of signposts to help point you in the right direction.